Investigating Household Knowledge, Attitudes, and Practices in Solid Waste Segregation, Recycling and Management: A Study of Kathmandu Metropolitan City - Aryal, Prativa; Adhikari, Prapti (MVIC Journal of Management and Information Technology, 2025)
Globally, 2.6 billion people in the world do not use proper methods of waste disposal. Some 1.1 billion people still dispose of waste in open places, thus facing many health-related problems. In Nepal too, currently, around 450 metric tons of solid waste are generated in Kathmandu every day. In such a context, the objective of this study is to assess household knowledge, attitudes, and practices related to solid waste segregation, recycling, and management in Kathmandu Metropolitan City. With a substantial sample size of 1400 households, the study provided a comprehensive analysis of current waste management behaviors. The results suggest that households with knowledge about waste segregation have good solid waste management practices, including reuse and recycling, while controlling for other socio-economic covariates. This paper concludes that providing information on waste segregation and other waste management-related aspects could potentially encourage households to adopt good solid waste management practices. The waste collectors are found to be the best channel to disseminate such information.